Why Are Whimbrels Not Advancing Their Arrival Dates Into Iceland? Exploring Seasonal and Sex-Specific Variation in Consistency of Individual Timing During the Annual Cycle - Carneiro, Camilo; Gunnarsson, Tómas G.; Alves, José A. (Frontiers in Ecology and Evolution, 2019)
The timing of annual events is key for organisms that exploit seasonal resources,as deviations from optimal timing might result in considerable fitness costs. Under strong time selection,individuals likely have fewer suitable strategies available than when selection is more relaxed,hence both consistency and flexibility might be advantageous depending on the life history or annual cycle stage. For migrants using both the arctic and the tropics during their annual cycle,the faster warming at higher latitudes than elsewhere in the range may lead to mismatches with local environmental conditions. Additionally,while individuals might already be limited in responding to changes at each stage,the potential degree of a given response will likely also be limited by responses at previous stages of the annual cycle. Contrary to other migratory waders breeding in Iceland,Icelandic whimbrels Numenius phaeopus islandicus have not changed arrival dates during the past 30 years,suggesting high individual consistency in spring arrival timing and a potential limitation in responding to a changing environment. After repeatedly tracking 12 individual Icelandic whimbrels at least twice throughout their annual cycle between 2012 and 2018, we investigated individual consistency of spring arrival date and other annual stages and migration strategy,and explored differences between sexes and seasons. Individuals were more consistent on timing of spring than autumn migration,and the most consistent stage was departure from the wintering sites. Timing of laying was the stage that varied the most,and no overall significant difference between sexes was observed,except on spring stopover duration. While lower consistency in laying dates might allow individuals to track the advancement of spring, consistency at departure from the wintering sites, stopover duration, and arrival into Iceland might limit the degree of advancement. Transgenerational changes in the migratory behaviour of other wader species allows population level responses to a changing phenology,but seems unlikely for Icelandic whimbrels, given the stable dates of spring arrival in this population. Under continuing advancement of spring onset,it is thus important to acquire information on the timing of spring arrival of recruits and on the ontogeny of migration to understand how migratory schedules are defined and might influence responses of long-distance migrants to environmental change.